DRUG INVENTORY CONTROL USING THE ABC-VEN METHOD AT HEALTH SERVICE UNITS IN KARAWANG CITY - Ani Sakila; Dicky Suryapranatha; Decut Della Oganda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Uncontrolled drug inventory is a significant challenge in health services, especially in remote areas, resulting in high rates of expired drugs and budget waste. The mismatch between drug stock and needs can disrupt the quality of health services provided to the community. This study aims to analyze drug inventory control using the ABC-VEN combination method, which groups drugs based on consumption value and level of medical importance. The methods applied include observation, interviews, documentation, and analysis of drug use data from July to December 2024. The ABC analysis categorizes drugs into three groups based on investment value: A (70%), B (21%), and C (9%). Meanwhile, the VEN analysis classifies drugs as Vital (13%), Essential (59%), and Non-Essential (27%). The results of the ABC-VEN combination show that 17% of drug items are included in the priority group, 46% in the main group, and 38% in the additional group. These findings provide a strong basis for determining priorities in drug procurement and supervision. The conclusion of this study confirms that the ABC-VEN method has proven effective in increasing the efficiency of inventory management, reducing the risk of expired drugs, and supporting more rational decision-making in drug procurement.